ALA_PDT Promotes Ferroptosis-Like Death of Mycobacterium abscessus and Antibiotic Sterilization via Oxidative Stress - Xiaoyu Wang; Meiyin Wan; Lei Zhang; Yongdong Dai; Yang Hai; Chenda Yue; Junqi Xu; Yadan Ding; Mei Wang; Jianping Xie; Xia Lei; Julia-Li Zhong (MDPI AG, 2022)
Mycobacterium abscessus is one of the common clinical non-tuberculous mycobacteria (NTM) that can cause severe skin infection. 5-Aminolevulinic acid photodynamic therapy (ALA_PDT) is an emerging effective antimicrobial treatment. To explore whether ALA_PDT can be used to treat M. abscessus infections, we conducted a series of experiments in vitro. We found that ALA_PDT can kill M. abscesses. Mechanistically, we found that ALA_PDT promoted ferroptosis-like death of M. abscesses, and the ROS scavenger N-Acetyl-L-cysteine (NAC) and ferroptosis inhibitor Ferrostatin-1 (Fer-1) can mitigate the ALA_PDT-mediated sterilization. Furthermore, ALA_PDT significantly up-regulated the transcription of heme oxygenase MAB_4773, increased the intracellular Fe2+ concentration and altered the transcription of M. abscessus iron metabolism genes. ALA_PDT disrupted the integrity of the cell membrane and enhanced the permeability of the cell membrane, as evidenced by the boosted sterilization effect of antibiotics. In summary, ALA_PDT can kill M. abscesses via promoting the ferroptosis-like death and antibiotic sterilization through oxidative stress by changing iron metabolism. The study provided new mechanistic insights into the clinical efficacy of ALA_PDT against M. abscessus.